Formative Assessment Practices in Special School Classrooms With the Support of E-Books: A Case Study - Yan, Zi; Xiao, Yangyu; Sin, Kuen-Fung; Yang, Lan; Guo, Wu-Yuan (Frontiers in Education, 2021)
While formative assessment is recognised as a powerful strategy to improve student learning in mainstream education, less is known about its use in special schools. This study investigates how teachers’ Personal Practice Assessment Theories (PPATs) affect their formative assessment practices within the special school context with the support of e-books. A case study was conducted with three Chinese teachers working with lower primary students who exhibit mild levels of intellectual disability. Data were collected through classroom observations and interviews. The findings reveal that the interaction between teachers’ PPATs and the e-learning environment affect teachers’ assessment goals, and the way they ‘elicit’, ‘interpret’ and ‘respond’ to assessment information. This study contributes to the understanding of how e-learning technology can be used to facilitate meaningful formative assessment in the special education context.